On common terms with shared risks – Studying the communication of risk between local, regional and national authorities in Sweden. (September 2015) - Månsson, Peter; Abrahamsson, Marcus; Hassel, Henrik; Tehler, Henrik
Abstract: Uncommon categorization, i.e. disparities in how similar terms and information is interpreted, coded and categorized, has been shown to impede inter-agency communication and collective sense-making. This study focuses on the presence and effects of uncommon categorizations in disaster risk management systems. We use the Swedish disaster risk management system as our case, and our empirical data consist of more than 120 reports from risk and vulnerability assessments, supplemented by 45 semi-qualitative interviews with officials who are involved in the realization of such assessments. Apart from investigating the causes and effects of uncommon categorization, we also map its extent and character, and its development between the years 2010 and 2014. The study shows that uncommon categorization is prevalent in the Swedish disaster risk management system. We argue that this has an extremely detrimental effect on the ability to integrate risk information, resulting in less useful bases for decisions and, thus, in a less efficient disaster risk management system. Nevertheless, we can also see signs of a reduction in uncommon categorization in recent years.